Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1117/1.3558727
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence emission and polarization analyses for evaluating binding of ruthenium metalloglycoclusters to lectins and tetanus toxin C-fragment

Abstract: Abstract. We develop a fluorescent ruthenium metalloglycocluster for use as a powerful molecular probe in evaluating the binding between carbohydrates and lectins by fluorescence emission (FE) and fluorescence polarization (FP) analyses. Changes in the FE and FP of these metalloglycoclusters are measured following the addition of lectin [peanut agglutinin (PNA), Ricinus communis agglutinin 120, Concanavalin A (ConA), or wheat germ agglutinin] or tetanus toxin c-fragment (TCF). After the addition of PNA, the FE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…We also confirmed that our metalloglycocluster is useful for evaluating the specific binding between carbohydrates and lectins using fluorescent correlation spectroscopy, an approach which can measure a single molecular binding event (unpublished data). Furthermore, we confirmed the presence of the clustering effect using metalloglycoclusters with controlled clusterization of the carbohydrate (26).…”
Section: D-1 Affinity Evaluation Using Metalloglycoclusterssupporting
confidence: 70%
“…We also confirmed that our metalloglycocluster is useful for evaluating the specific binding between carbohydrates and lectins using fluorescent correlation spectroscopy, an approach which can measure a single molecular binding event (unpublished data). Furthermore, we confirmed the presence of the clustering effect using metalloglycoclusters with controlled clusterization of the carbohydrate (26).…”
Section: D-1 Affinity Evaluation Using Metalloglycoclusterssupporting
confidence: 70%
“…Fluorescence emission spectra of lectins are sensitive to specific and nonspecific ligands. 33 The intrinsic fluorescence of BMSL, originating from the tryptophan and tyrosine residues, was observed at 337 nm. Figure 1A shows that the fluorescence emission intensity located at 337 nm decreases upon titration with AgNPs, suggesting an interaction between BMSL and AgNPs.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…274,282 Multivalent metal-based glycoclusters have been synthesized using Ru(II) complexes with three bi-pyridine moieties conjugated with lactose or maltose (Figure 100). 283,284 The complexes displayed a red-shifted emission peak in the presence of selective lectins, probably as a result of binding of the Ru(II) complex to a hydrophobic pocket of the lectin. A supramolecular strategy was described using a host-guest interaction between an adamantyl-Ru(II) complex and heptamannosylated β-CD to provide fluorescence sensors with up to 42 carbohydrate copies.…”
Section: Glycoconjugates Based On Metal-centered Cores For Biomedicalmentioning
confidence: 99%